2021
DOI: 10.1149/1945-7111/ac2e1d
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Contamination of the Praseodymium Doped Ceria Oxygen Surface Exchange Coefficient

Abstract: Chemical oxygen surface exchange coefficients are used to quantify and rank the performance of oxygen exchange catalysts used in solid oxide fuel cell, solid oxide electrolysis cell, oxygen separation membrane, catalytic converter, and other oxygen-exchange-enabled devices. Unfortunately, during the manufacture and operation of these devices it is easy to introduce siliceous contaminants that degrade their oxygen exchange performance. Surprisingly, despite the well-known negative impact siliceous impurities ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 71 publications
(97 reference statements)
2
9
0
Order By: Relevance
“…[ 12,54–56 ] Recently, Ma et al found that even if the siliceous surface phase is only a few nanometers thick, the chemical oxygen surface exchange coefficient of PCO decreases by ≈3 orders of magnitude and the activation energy is doubled. [ 57 ] In the context of this work, it is interesting to relate our findings for the selected levels of silica infiltration with what might be typical in applications. Horita et al., for example, examined the effects of impurities on the performance degradation of flatten tubular SOFC cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12,54–56 ] Recently, Ma et al found that even if the siliceous surface phase is only a few nanometers thick, the chemical oxygen surface exchange coefficient of PCO decreases by ≈3 orders of magnitude and the activation energy is doubled. [ 57 ] In the context of this work, it is interesting to relate our findings for the selected levels of silica infiltration with what might be typical in applications. Horita et al., for example, examined the effects of impurities on the performance degradation of flatten tubular SOFC cells.…”
Section: Discussionmentioning
confidence: 99%
“…18 In line with the findings of Nicollet et al, the relaxation kinetics of PCO onto which Si-species had been added to the surface responded considerably slower to stepwise oxygen changes than the pristine material, Figure 4B (blue). 3,18,27,43,44 On the other hand, the basic additive lithia, resulted in an increased response rate, see Figure 4B (yellow). The addition of these two surface additives, resulted in a variation of k chem (derived from an analysis of relaxation profiles) by 6 orders of magnitude.…”
Section: Oxide Additives-solid Oxide Fuel Cell Cathodesmentioning
confidence: 98%
“…For example, Si-species are recognized as an ubiquitous poison in metal oxide processing steps, for example, originating from furnace refractories and sealants/greases. 3,27 The widespread use of volatile organic silicon compounds (VSCs) in consumer products, for example, in electronics, furniture, healthcare, pharmaceuticals, cosmetics, and cookware, is already known to degrade SMOX-based sensors 8,22,27 ; and therefore there is a significant push in the industry to develop stable sensor options. 3,8 Si-species are known to significantly degrade SOFC cathode materials as well.…”
Section: Physical Blockingmentioning
confidence: 99%
See 2 more Smart Citations